Toward a universal quantum QSPR operator. Issue 15 (19th February 2018) - Carbó‐Dorca, Ramon
Abstract: This article presents a discussion about the formalism, which might be associated to a general Quantum quantitative structure–properties relations operator, appearing in a Boltzmann‐like exponential form, which is based in turn on the definition of the concept of thermal voltage, applied to thermally scaled electronic density functions. Three practical numerical examples are presented, corresponding to the calculation of the polarization angle in assorted chiral molecules, the estimation of fish toxicity for perchlorobenzene within the set of chlorobenzenes and a typical quantum QSAR study on the popular Cramer steroid set. Abstract : The thermal voltage concept, which has been used for a long time in solid state lore, is employed to develop a general formalism, tending to provide the so‐called quantitative structure–properties relations from a quantum theoretical point of view. In this way, thermal voltage permits first to define a homothetic scaling of quantum electronic density functions. Three application examples in the domain of chirality, toxicity, and biological activity are provided. Original Drawing by Pep Camps (Painter from Girona).